Effect Of Process Parameters On Quality Of Surface Cleaned By Electrolyte Plasma Processing - S. J. Parihar, S. T. Purkar (International Journal of Advanced Science and Technology, 2020)
Electrolyte plasma was generated between two electrodes immersed in an electrolyte of 12% NaHCO3. Disc shaped AISI1018 steel specimens of 12.7 mm diameter and 8.96mm height were used for the experimentation. Electrolyte flow rate of 2 L/min was used, and the anode-cathode separation distance was set to 5 mm. For determining the effect of separation distance, spacings of 3, 4, 5, 7.5, and 10 mm were chosen. When varying the concentration of the electrolyte, concentrations of 8, 10, and 12 wt. % were selected, and flow rate variations were 2, 0.8, 0.5, and 0.3 L/min. SEM study was performed to examine the effect of various parameters on the surface quality of the cleaned disc specimens Keywords: Electrolyte plasma, SEM, surface morphology.